2014
DOI: 10.1021/jo502096t
|View full text |Cite
|
Sign up to set email alerts
|

Four-Component Bicyclization Approaches to Skeletally Diverse Pyrazolo[3,4-b]pyridine Derivatives

Abstract: A novel four-component bicyclization strategy has been established, allowing a flexible and practical approach to 37 examples of multicyclic pyrazolo[3,4-b]pyridines from low-cost and readily accessible arylglyoxals, pyrazol-5-amines, aromatic amines, 4-hydroxy-6-methyl-2H-pyran-2-one, and cyclohexane-1,3-diones. The polysubstituted cyclopenta[d]pyrazolo[3,4-b]pyridines were stereoselectively synthesized through a microwave-assisted special [3+2+1]/[3+2] bicyclization with good control of the spatial configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…[ 13 ] Additionally, they act as liquid crystals, [ 14 ] semiconductors, [ 15 ] and organic light‐emitting diodes. [ 16 ] Pyrazole and its analogs have also received considerable attention because of their synthetic application as chiral auxiliaries, [ 17 ] reagents in various multicomponent reactions, [ 18 ] and guanylating agents. [ 19 ] From the literature survey, it has also revealed that substituted pyrazoles are also utilized as chelating agents for the detoxification of undesired metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Additionally, they act as liquid crystals, [ 14 ] semiconductors, [ 15 ] and organic light‐emitting diodes. [ 16 ] Pyrazole and its analogs have also received considerable attention because of their synthetic application as chiral auxiliaries, [ 17 ] reagents in various multicomponent reactions, [ 18 ] and guanylating agents. [ 19 ] From the literature survey, it has also revealed that substituted pyrazoles are also utilized as chelating agents for the detoxification of undesired metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Similarly, the four-component reaction of arylglyoxal, aminopyrazole, aromatic amine, and dimedone/4-hydroxy-6-methyl-2-pyrone provide either tetracyclic or tricyclic fused heterocycles (Scheme 1, Equation 4). [35] Considerable attention has been paid in recent times to the development of new multicomponent reactions (MCRs) with arylglyoxals because of their interesting reaction behavior. [36][37][38][39][40] After a literature survey on the interesting reactivity patterns of arylglyoxals with aminopyrazoles, and in continuation of our…”
Section: Previous Workmentioning
confidence: 99%
“…Tu et al. reported the four‐component reaction of phenylglyoxal, 7 , 4‐hydroxy‐6‐methyl‐2 H ‐pyran‐2‐one 9 , and aniline, which could be used to synthesize multicyclic pyrazolo[3,4‐ b ]pyridine 10 (Scheme ) . The authors proposed a mechanism in which the initial event of the reaction was the condensation of 9 and aniline.…”
Section: Aliphatic Axb3 Smentioning
confidence: 99%